Seeking to Serve or $erve? Hispanic-Serving Institutions' Race-Evasive Pursuit of Racialized Funding - Stephanie Aguilar-Smith (SAGE Publishing, 2021)
This critical qualitative study explores Hispanic-serving institutions' (HSIs) pursuit of racialized federal funds and theorizes the connection between grant seeking and servingness at HSIs. Specifically, the study's guiding research question was: Why do HSIs pursue racialized Title V funding? Based on interviews with 23 institutional actors at 12 HSIs, including public Hispanic-serving community colleges and both public and private 4-year institutions, the findings suggest that HSIs vie for Title V grants for assorted and, at times, conflicting reasons. Specifically, they seek this racialized funding to (a) pool money, (b) address broad-based institutional needs, (c) signal legitimacy, and (d) support all students. Importantly, some of the reasons have little to do with immediately serving students generally or Latinx students more specifically. Thus, I argue that in their race-evasive pursuit of Title V funds, many HSIs capitalize on their Latinx students, rendering serving into $erving and ghosting the "H" and "S" in HSIs.